1997
DOI: 10.1097/00001756-199707280-00010
|View full text |Cite
|
Sign up to set email alerts
|

Extra-junctional localization of glutamate transporter EAAT4 at excitatory Purkinje cell synapses

Abstract: We used silver-enhanced immunogold electron microscopy to reveal synaptic localization of the glutamate transporter EAAT4 in mouse cerebellar Purkinje cells (PCs). Gold-silver particles representing the EAAT4 were densely localized on extra-junctional membrane, but not on junctional membrane of PC spines in contact with parallel fiber or climbing fiber terminals. No particle accumulations were observed at inhibitory synapses formed on cell body and dendritic shafts of PCs. Therefore, the EAAT4 is selectively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…The other component, termed ''residual current,'' has several features inconsistent with glutamate transport. First, we have confirmed that the residual current is not blocked by high concentrations of TBOA, a competitive antagonist for EAAC1 and EAAT4 (36,37), the two EAATs expressed by PCs (12,14,24,38). Second, I-V analysis of the residual synaptic and photolysis-evoked currents shows that they uniformly reverse polarity at potentials near 0 mV, which would not be expected of stoichiometric EAAT currents or of responses consisting of mixed stoichiometric and anion currents.…”
Section: Discussionsupporting
confidence: 57%
“…The other component, termed ''residual current,'' has several features inconsistent with glutamate transport. First, we have confirmed that the residual current is not blocked by high concentrations of TBOA, a competitive antagonist for EAAC1 and EAAT4 (36,37), the two EAATs expressed by PCs (12,14,24,38). Second, I-V analysis of the residual synaptic and photolysis-evoked currents shows that they uniformly reverse polarity at potentials near 0 mV, which would not be expected of stoichiometric EAAT currents or of responses consisting of mixed stoichiometric and anion currents.…”
Section: Discussionsupporting
confidence: 57%
“…In the cerebellar cortex, both GLAST and EAAT4 are abundantly expressed as predominant glial and neuronal transporters, respectively (Danbolt, 2001). GLAST is located on the plasma membranes of Bergmann glial processes surrounding the excitatory synapses in Purkinje cells (PCs) (Rothstein et al, 1994;Chaudhry et al, 1995), whereas EAAT4 is concentrated in extrasynaptic regions at excitatory synapses in PCs (Tanaka et al, 1997;Dehnes et al, 1998). This different distribution of GLAST and EAAT4 at the electron microscopic level suggests that these transporters serve distinct functions in excitatory synapses on PCs.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the five characterized glutamate transporters, excitatory amino acid carrier 1 (EAAC1) (Kanai and Hediger, 1992) and excitatory amino acid transporter 4 (EAAT4), have been reported to be expressed in Purkinje neurons (Kanai et al, 1995;Furuta et al, 1997;Dehnes et al, 1998) (but see Tanaka et al, 1997a). G TA can be detected upon activation of climbing fiber synaptic inputs and elicited in membrane patches by glutamate application (Otis et al, 1997).…”
mentioning
confidence: 99%